Consequences of changing the electoral system for the model of political competition – The case of the 2018 elections to municipal councils in Łódź Voivodeship - Onasz, Maciej; Klonowski, Michał; Włodarska-Frykowska, Agata (Eastern Review, 2021)
The article is an attempt to assess the effects of the 2018 reform of local electoral law on a medium scale. The main goal is to investigate the consequences of these changes for the model of political rivalry. Through the use of a selection of quantitative methods, the authors verify hypotheses regarding the proportionality of local elections and the mechanical effect of the electoral system. The overall aim is to establish to what extent the new electoral system deforms the voting results when distributing seats among the electoral committees. Apart from the hypotheses, the authors also verify whether Łódź Voivodeship is a suitable case study and representative of national trends.